A Novel Function of Mitochondrial Phosphoenolpyruvate Carboxykinase as a Regulator of Inflammatory Response in Kupffer Cells - Dong, Haibo; Feng, Yue; Yang, Yang; Hu, Yun; Jia, Yimin; Yang, Shu; Zhao, Nannan; Zhao, Ruqian (Frontiers in Cell and Developmental Biology, 2021)
Background: There has been a recent appreciation that some metabolic enzymes can profoundly influence the nature of the immune response produced in macrophages. However, the role of mitochondrial phosphoenolpyruvate carboxykinase (PCK2) in immune response remains unknown. This study aims to investigate the role of PCK2 in lipopolysaccharides (LPS)-induced activation in Kupffer cells. Methods: Inflammatory cytokines were determined by real-time quantitative reverse transcription-polymerase chain action (qRT-PCR) and flow cytometric analysis using a cytometric bead array. Western blotting and immunofluorescence staining were used to determine PCK2 expression and subcellular distribution under confocal laser microscopy. qRT-PCR, flow cytometry, and high-performance liquid chromatography (HPLC) were used to determine mitochondrial function. Pharmacological inhibition, knockdown, and overexpression of PCK2 were used to confirm its function. Co-immunoprecipitation (Co-IP) was performed to determine MAPK/NF-κB phosphorylation. Results: Inflammatory response was significantly increased in LPS-treated mice and Kupffer cells. During the inflammatory process, the protein level of PCK2 was significantly upregulated in Kupffer cells. Interestingly, the localization of PCK2 was mainly in cytosol rather than mitochondria after LPS stimulation. Gain-of-function and loss-of-function analyses found that PCK2 overexpression significantly upregulated the levels of inflammation markers, whereas PCK2 knockdown or inhibition significantly mitigated LPS-induced inflammatory response in Kupffer cells. Furthermore, PCK2 promoted protein phosphorylation of NF-κB and AKT/MAPK, the major signaling pathways, controlling inflammatory cascade activation. Conclusion: We identified a novel function of PCK2 in mediating LPS-induced inflammation and provided mechanistic insights into the regulation of inflammatory response in Kupffer cells. Therefore, PCK2 may serve as a novel therapeutic target for the regulation of Kupffer cells-mediated inflammatory responses.